Poverty of religious institute in relation to the issue of Church goods - DOMASZK, ARKADIUSZ (Prawo Kanoniczne, 2013)
Religious institutes are a special sign of faith for the whole world. This includes public testimony of religious gave to Christ and the Church. Poverty in religious institutes has an individual dimension, but also common one. This paper discusses the communal aspects of vow of poverty, confronted with the concept of Church goods. Religious goods require good management. The decisions of the stewards and the superiors, or other eligible persons should be greatly responsible. Above mentioned goods belong not to natural persons, nor to private persons, but to a public legal person, which acts on behalf of the Church. Due to the authority of the Church, a board of directors managing religious goods demands not only a careful applying legal norms, canonical and civil, but also the social doctrine of the Church and respecting moral principles. These recommendations should apply to both, the ordinary board and extraordinary, as well as to the financial obligations and debts. The scope of the commons goods includes also those the goods, which are acquired by religious for the institute’s use: "whatever acquires religious - acquires monastery". This also concerns means resulting from employment, wages, allowances, or insurance. Since religious institutes are a public legal persons, they have the right to acquire, hold, manage and alienate Church goods. All activities taken by the institutes and their representatives in that scope should express a testimony of faith. A communal testimony on the vow of poverty shows its spiritual dimension. This constitutes an important message for the modern world showing the need and ability to maintain detachment from the possession of material goods.